Development and Validation of Urological and Appearance Domains of the Post-Affirming Surgery Form and Function Individual Reporting Measure (AFFIRM) for Transwomen following Genital Surgery. Issue 6 (21st December 2021) - Huber, Sarah; Ferrando, Cecile; Safer, Joshua D.; Pang, John Henry Y.; Streed, Carl G.; ,; Priestley, Jennifer; Culligan, Patrick
Abstract : Purpose: As feminizing gender-affirming surgery becomes increasingly accessible, functional outcomes are increasingly relevant. We aimed to develop and validate the first patient-reported outcome questionnaire focusing on postoperative symptomatology and quality of life. Material and Methods: Questions were developed from interviews with postoperative transwomen followed by face validation from a multispecialty clinician group. The measure was co-administered with established relevant questionnaires for concurrent validity testing. Participants were asked to complete the questionnaire at baseline and at a 2-week retest interval. Results: The AFFIRM questionnaire is a 33-item patient-reported outcome measure comprising Appearance, Urological and Gynecologic domains, each scored to create a composite AFFIRM score. A total of 102 women participated, with 60% completing the test-retest. The overall Cronbach's α for AFFIRM was 0.79, and domain α for AFFIRM-A, AFFIRM-U and AFFIRM–G was 0.85, 0.87 and 0.42, respectively. Test-retest demonstrated score reliability (z values −1.862 to −0.005, p >0.05) with intraclass coefficients demonstrating moderate to good absolute correlation (0.54 to 0.88). The AFFIRM-A and AFFIRM-U correlated well with the Genital Appearance Satisfaction Measure and Urinary Distress Inventory-6, respectively (ρ 0.556 and 0.618, p <0.001); 89% of participants confirmed congruence between their external genitalia and gender identity, 87.8% reported clitoral sensation and 75.6% expressed satisfaction with vaginal caliber. Reported symptoms included a misdirected urinary stream (68.9%), nocturia (51.3%), urinary frequency (29.7%) and vaginal pain (46.7%). Conclusions: Transwomen have diverse symptoms not captured by unstructured questions or cisgender questionnaires. The AFFIRM questionnaire is the first tool available to reliably evaluate outcomes following feminizing gender-affirming surgery.